Identidade rural e agricultura familiar :O Pronaf B sob a ótica dos beneficiados - Vieira, Denes Dantas (2007)
This work has for objective to analyze the perception of benefited of Pronaf B Programa Nacional de Fortalecimento da Agricultura Familiar, in relation to the results that are presented concerning this program. For this, it is presented hypothesis of that the familiar agriculturists, fit in the norms of credit of Pronaf B, have a peculiar perception on the end item of this program, produced from inherent characteristics to the agricultural reality where they live. Ahead of this, I broke myself of estimated of that the searched familiar agriculturists are more socially vulnerable to the inaqualities the agricultural areas. For this research, they had been used, mainly, theoretical reflections of studious of the campesinato, familiar agriculture and of researchers of the impacts of Pronaf B in the agricultural way. The empirical data of the research had been gotten, through the application of questionnaires with the benefited ones and interviews with the mediators of this program in the two searched cities, Apodi and Antônio Martins, in the Rio Grande do Norte, who proportionally withholds the biggest contract number of Pronaf B in the state. The conclusion of the research ratifies the initial hypothesis of that the perception on the results of Pronaf B for benefited its is peculiar, and points stops beyond the economic results, such as: the rise of auto-esteem; the rescue of the citizenship feeling and as impact in autoconsumo of the families of the agriculturists benefited for Pronaf B